Understanding individual experiences of COVID-19 to inform policy and practice in higher education : helping students, staff, and faculty to thrive in times of crisis - Bergerson, Amy Aldous; Coon, Shawn R. (New York, NY : Routledge, 2022)
"Utilizing findings from over 200 interviews with students, staff, and faculty at a US university, this volume explores the immediate and real-life impacts of COVID-19 on individuals to inform higher education policy and practice in times of crisis. Documenting the profound impacts that COVID-19 had on university operations and teaching, this text foregrounds a range of participant perspectives on key topics such as institutional leadership and loss of community, managing motivation and the move to online teaching and learning, and coping with the adverse mental health effects caused by the pandemic. Far from dwelling on the negative, the volume frames the lived experiences and implications of COVID-19 for higher education through a positive, progressive lens, and considers how institutions can best support individual and collective thriving during times of crisis. This text will benefit researchers, academics, and educators in higher education with an interest in the sociology of education, higher education management, and eLearning more broadly. Those specifically interested in student affair practice, as well as the administration of higher education, will also benefit from this book. Amy A. Bergerson is Professor of Educational Leadership and Policy, Senior Associate Dean of Undergraduate Studies, and Director of the Office for Student Success and Empowerment at the University of Utah, USA. Shawn R. Coon is Graduate Research Assistant in the department of Educational Leadership and Policy at the University of Utah, USA"--
Introduction / by Amy Aldous Bergerson & Shawn R. Coon -- Thriving as a lens for understanding the impact of COVID-19 on higher education faculty, staff, and students / by Amy Aldous Bergerson & Latu Kinikini -- Interpretive analysis as a window into individual experiences / by Shawn R. Coon & Amy Aldous Bergerson -- Teaching online and caring for students during a global pandemic / by Willie Chen, Denise Brenes, & Amy Aldous Bergerson -- Community, communication and expectations for teaching / by Willie Chen, Denise Brenes, & Amy Aldous Bergerson -- Pandemic privilege / by Amy Aldous Bergerson & Shawn R. Coon -- Working from home challenges : resources, tools, and quality / by Bobbi Davis & Amy Aldous Bergerson -- Loss of organic community and decentralized communications / by Sierra Stevens & Shawn R. Coon -- The burnout warning / by Marilisa Vega & Shawn R. Coon -- Online learning during COVID / by Diane Lê Strain, Mayumi Kasai, & Chris Wallace-Carrete -- Mental health, motivation, and emotions / by Jessi Gerowitz, Karla Motta, & Marilisa Vega -- Connectivity, community, and sense of belonging / by Shenrui Yang, Karla Motta, & Jessi Gerowitz -- Complications for institutional thriving across stakeholders / by Christopher Wallace-Carrete, Amy Aldous Bergerson, & Shawn R. Coon -- The way forward : rethinking thriving in crisis / by Shawn R. Coon & Amy Aldous Bergerson.
Keywords: Universities and colleges -- United States -- Administration; Education, Higher -- Social aspects -- United States; COVID-19 Pandemic, 2020- -- Social aspects -- United States; College students -- United States -- Attitudes; Universities and colleges -- United States -- Professional staff -- Attitudes; College teachers -- United States -- Attitudes; EDUCATION / Higher; EDUCATION / Organizations & Institutions